The Impact of Brain Rot on Students Anxiety and Learning Focus : Literature Review - Adhelia Husnainy Zaen; Dewi Sulastri; Ahmaddin Ahmad Tohar; Khairil Anwar (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The phenomenon of brain rot has emerged as a growing concern among university students due to excessive exposure to digital media such as TikTok, Instagram, and YouTube, which may impair attention, self-regulation, and cognitive performance. This study aims to examine the relationship between brain rot, anxiety, and learning focus among university students, and to explore its implications from both psychological and Islamic perspectives. This research uses a literature review approach by analyzing journals, books, and scientific reports published between 2017 and 2025, focusing on studies related to digital media use, cognitive decline, and student well-being. The findings indicate that excessive digital consumption correlates with higher levels of anxiety, reduced attention span, impaired executive functions, and lower academic motivation. The study emphasizes the importance of digital literacy, screen time management, and self-awareness interventions to mitigate brain rot and maintain students' mental and academic well-being.